PENGARUH TEKANAN WAKTU, LOCUS OF CONTROL , TINDAKAN SUPERVISI, DAN MATERIALITAS TERHADAP PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT - Sulastiningsih Sulastiningsih; Intan Ayu Candra (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
The purpose of this study is to prove: (1) Time pressure, locus of control, the action of supervision and materiality partially affect the premature termination of the audit procedures (2) Time pressure, locus of control, supervision and materiality simultaneously affect the premature termination on the audit procedures. This research was conducted in Public Accountant firm in Yogyakarta region of which total 12 samples of KAP, by distributing 105 questionnaires, and 57 questionnaires were returned (54%). 34 of the returned questionnaires can be processed (34%). The samples in this study were determined by using non-probability sampling, one of purposive sampling methods. Data analysis consisted of: (1) validity test, reliability test and classical assumption. The result showed that the instruments used are quite reliable and valid (2) multiple linear regression analysis. The results are (a) Some of independent variables partially affect premature termination of the audit procedure, while the action of supervision does not influence premature termination of audit procedures (b) All independent variables influence simultaneously to the premature termination of the audit procedures (c) All independent variables showed that as much as 55% it affects on premature termination of the audit procedures, the rest of it are influenced by other variables. (3) Friedman Test. The result shows that there are order of priority of audit procedures being terminated.